Gerontology education offerings: experiences of Iowa Human Sciences Extension and Outreach educators. Issue 12 (1st December 2020) - Meinertz, Naomi R.; Sellers, Debra M.; Schainker, Lisa M.; Lee, Jeong Eun
ABSTRACT: Iowa State University Human Sciences Extension and Outreach (HSEO) provides informal educational opportunities to older adults and their families in rural Iowa within the subject areas of family life, family finance, and nutrition and wellness. The successful implementation of educational opportunities is partially determined by the knowledge of HSEO educators who connect with rural older adults. Although past literature has identified gaps of transportation issues and healthcare access for older adults in rural areas, we aimed to extend this literature to understand rural aging experience through the perspective of Iowa State University HSEO educators' interaction with rural older adults. We outline the Extension model as a national system and as part of the land-grant university, together with the role it plays in providing community-based education to support the health and well-being of rural older adults and their families. In 2018, 28 HSEO educators completed the revised Fraboni Scale of Ageism, which assessed their ageism levels. Results indicated relatively low levels of ageism ( M = 37.75, SD  = 7.44). Follow-up interviews with a subsample of 13 educators were conducted to delineate perceived barriers and needs for alternative delivery and marketing methods to improve outreach in rural areas. Results from this study will be used to inform the creation, implementation, and evaluation of new educational offerings within Iowa State University Extension and Outreach, with the goal to improve the well-being of older adults and their families in rural Iowa. We provide recommendations for other professionals who work with older adults in rural areas.